Dynamics and Structure of Money Expenses in Families of Soviet Workers and Employees in 1946-1991 (on Materials of Sverdlovsk Region) - V. N. Mamyachenkov (Научный диалог, 2017)
The article is devoted to the interesting subject relatively little developed in the national historiography. The study is conducted on the material of several archives: State Archive of Sverdlovsk Region, Archive of the Territorial body of Federal State Statistics Service and the Center of documentation of public organizations of Sverdlovsk region. This allowed the author to develop and present his own concept of the research topic. The topic urgency is due to its high relevance to the social siences, primarily to history, economics, sociology and political science. Scientific novelty of the work is seen in the fact that the new material discovered by the author in these archives is introduced into scientific usage. It is stated that the analysis of money expenses of citizens is an important direction of research in the sphere of material conditions of their lives. It is alleged that during the whole researched period, the leading role in the structure of costs of family budgets of the population of Sverdlovsk oblast played the costs of purchasing food, and expenditures on the acquisition of clothes and shoes were the second in importance. It is proved that the expenditure on cultural and educational needs during this period were negligible in the workers and employees. It is emphasized that the highest level of expenditure (and income) had families of engineering-technical workers of the regional center. It is declared that the class of industrial workers officially positioned in the country as hegemonic class according to its actual position in the USSR actually was not a class of such kind, judging by the level of its expenditures.